Splenic belly in a patient with myelofibrosis - Díaz Rodríguez, Priscila Milagros (2022)
A 70-year-old male, with a history of myelofibrosis secondary to polycythemia vera for 4 years, with treatmentof folic acid, acetylsalicylic acid and hydroxyurea. He went to the hospital emergency room for asthenia, weight loss of 10 kg for a year and intermittent abdominal pain in the left hypochondrium for a month.